The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1741143220901857
|View full text |Cite
|
Sign up to set email alerts
|

Core leadership practices of school principals in the Kingdom of Saudi Arabia

Abstract: This qualitative study aims to explore the core leadership practices of school principals in the Kingdom of Saudi Arabia. Given the exploratory nature of this study, a qualitative research design methodology was employed through which an in-depth, multi-perspective study of the practices of four secondary school principals was carried out. Employing a semi-structured interview protocol developed specifically for this study, data was collected from the principals and four teachers and four parents from each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…One notable gap relates to the impact of culture on principals’ leadership and management practices across GCC societies. There is emerging evidence suggesting that culture shapes how school principals conceptualise effective leadership (see Alqahtani et al, 2020) and that specific cultural contexts create specific challenges for school leaders in the region (see Alsaleh, 2019; Hammad and Shah, 2018). Other important gaps include the impact of principal leadership on school operations and outcomes, especially student learning and achievement, as well as the impact of principal leadership on teachers’ professional learning and development.…”
Section: Discussionmentioning
confidence: 99%
“…One notable gap relates to the impact of culture on principals’ leadership and management practices across GCC societies. There is emerging evidence suggesting that culture shapes how school principals conceptualise effective leadership (see Alqahtani et al, 2020) and that specific cultural contexts create specific challenges for school leaders in the region (see Alsaleh, 2019; Hammad and Shah, 2018). Other important gaps include the impact of principal leadership on school operations and outcomes, especially student learning and achievement, as well as the impact of principal leadership on teachers’ professional learning and development.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers (Aas and Brandmo, 2016; Daniels et al, 2019; Leithwood et al, 2020) argued that leadership practices should be studied from an integrative perspective, combining theories such as those of instructional, distributed and transformational leadership, instead of studying solely one fixed leadership theory. For instance, Alqahtani et al (2020) and Noman et al (2018) chose the integrative perspective of leadership practices and explored the leadership practices of school principals in Saudi Arabia and Malaysia respectively. In addition to this focus on leadership practices, Leithwood et al’s (2020) review showed that there is little understanding of how school principals enact leadership practices, and they call for further exploration of how school principals enact certain practices.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Here, HEIs are recognized to involve formal and informal rules of the game, embedded within which is the notion of gender as a binary social construct, involving appropriate (expected) actions on the role and identity of biological men and women (Al Alhareth et al., 2015). In terms of actors in Saudi Arabia's HEIs, the behaviors of both women and men are often shaped by the institutional practices and norms and stereotypical attitudes and behaviors, thereby posing issues and challenges for women's leadership (Alqahtani, 2021). In terms of the context, Saudi Arabia's HEIs do not function in a vacuum and are not immune to influences from the country's male‐dominated political, social, cultural, and economic environment (Lebeau & Alruwaili, 2021).…”
Section: Feminist Institutional Theorymentioning
confidence: 99%